Kesadaran dan Sikap Seorang Muslim Dalam Melaksanakan Tugas dan Fungsi Manusia - Deni Sopiansyah; Nurwadjah Ahmad; Andewi Suhartini (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
The current state of the world which is getting worse in terms of awareness as servants and shallow in terms of faith, this requires us to further increase our faith and devotion to Allah SWT. Increased faith and piety can work if done by people who are aware of their duties and roles as servants of Allah and the Caliph who convey the message of Da'wah from the Creator to all mankind. So we need an implementation in tiered and continuous learning through education Education is a process for self-development so that one is able to find a theory or skill so that one is able to internalize oneself in the form of cognitive, affective and psychomotor abilities into a single unit that cannot be separated in the process of Islamic education. The awareness and attitude of a Muslim will be able to give birth to humans who think in accordance with the Aqeedah, Shari'a and Akhlaq of Muslims, from the results of this thinking, humans are able to find a science that makes changes and human civilization